PENGARUH KUALITAS PELAYANAN TRANSPORTASI ‘SI BENTENG’ TERHADAP KEPUASAN MASYARAKAT DI KOTA TANGERANG - , Annisa Septiara Mujadilla; Arif Ginandjar Suryatman (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
Si Benteng public transportation is one of the modes of transportation in Tangerang City. In 2021 the Si Fortress transportation is operational until now with the hope that the public can enjoy this transportation comfortably and take it to their destination. However, the implementation of the Si Benteng transportation was not as expected for this service. The purpose of this study was to determine the effect of the quality of the fortress's transportation services on people's satisfaction in Tangerang City. In this study the authors used quantitative research methods with sampling techniques, namely random sampling techniques with data collection techniques using questionnaires or questionnaires. Data analysis techniques using validity and reliability tests. The results of the study show that it significantly has a strong and positive relationship to community satisfaction. The 25 questionnaire statements were declared valid and reliable, because the results of r count were greater than r tables and reliability test values. At the test value of the coefficient of determination of 84.8%, this has a large influence on the variable quality of service on community satisfaction variables. The conclusion from this study is that the quality of service has a very significant influence on the satisfaction of the Si Benteng transportation users.